ملاحظات بیهوشی در بیمار دختر هفده ساله مورد گرانولوماتوز وگنر - صحت, ملیحه; شریفی مفرد, مصطفی; حسینی امینی, محمدرضا `; سعیدی, محمد (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2019)
Wegener's granulomatosis is a systemic autoimmune vasculitis that is associated with vascular involvement and can affect any organ. The most important organs of involvement are kidneys, upper and lower respiratory tract. Because Wagner is a rare and dangerous disease, it can lead to death if not treated at the right time with medication and sometimes surgery with special anesthesia considerations. We report a 17-year-old female patient with Wegener's granulomatosis who scheduled thoracotomy surgery under general anesthesia with a diagnosis of bronchopulmonary fistula.